Knowledge and awareness of dental students on attention deficit hyperactivity disorder - Aditi Chopra; Veeraraghavan Vishnupriya; R Gayathri; S Kavitha (Wolters Kluwer Medknow Publications, 2022)
Attention deficit hyperactivity disorder (ADHD) is a prevalent psychiatric illness marked by a short span of attention, impulsive decisions, and behavioral issues. They are vulnerable to trauma and dental problems. The dental health team faces a challenge due to behavioral disorders, cognitive deficiencies, and short attention spans. At all stages of prevention and treatment, the management of these children necessitates various changes in approach. To collect data and analyze the awareness level of dental students toward ADHD. An online portal was used for the survey and distributed to 106 dentistry students with self-structured 10 questions. The findings were gathered through the survey portal, and graphs were drawn to compare the results. The SPSS software version 20.0 was used for statistical analysis. The Chi-square test was used to determine the correlation between the variables. Forty percent of those polled are aware of ADHD, which is a mental health condition characterized by excessively active and impulsive behavior. The symptoms of a child with ADHD are aware to 31.43% of voters. About 30.48% of the respondents know the symptoms of an adult with ADHD. About 29.52% of the respondents were aware of the causes of ADHD. To conclude that most dental undergraduates are not aware of the basic characteristics of ADHD. This means that there should be a spreading of knowledge on the subject. A dental student or dentist must know how to manage a patient diagnosed with ADHD. Careful management and treatment will lead to a satisfied and happy patient. Mismanagement may cause problems in the future for both the dentist and the patient.